Factors that affect speaking skills of students from ethnic minorities in English language learning - Nisrina, Nisrina (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
The idea of speaking skills is interconnected with the environment and social context of students poses new challenges by students from ethnic minorities in English language learning. These factors encompass the hindrances and the success of ethnic minority students in adjusting themselves in speaking classes. From 95 first-year students in English Language Teaching program, 18 of them have different minor ethnicities. This study adopted a qualitative study by using semi-structured interviews as an instrument of research. The data then transcribed, coded, and analyzed into different themes that are in line with the research objectives. The results of this study show that the difficulties experienced by students from ethnic minorities in adjusting themselves in speaking classes are the lack of confidence, shyness, and anxiety, speaking opportunities and vocabulary masteries, feeling isolated, and additive bilingualism from peers. However, these hindrances can be solved by various factors: teachers’ decision in designing discussed topics and speaking activities in classroom setting.